Doctor! Will I be dry? Factors determining recurrence after vesicovaginal fistula repair - Abdullah, Aziz; Syed, Sher Shah; Farooqui, Nuzhat; Siddiqui, Sajjad (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To evaluate various prognostic factors which determine outcome after surgical repair of VVF. Methods: A retrospective analysis of the record of 640 patients which underwent surgical repair of VVF during a period from Jan 2006 to June 2011. Multivariate analysis of the record was done using SPSS-19 software determining odds ratio with 95% confidence interval. Results: 640 patients underwent surgical repair of VVF. Overall success rate was 87.2%. Multivariate analysis determined that recurrence of VVF was significantly related to multiplicity (5 fold recurrence risk), pre-operative size of VVF (3 fold risk), secondary repair (3 fold risk) and etiology of the fistula (2 fold risk). Interposition of flap and delayed reconstruction was related to successful surgical outcome. Age, parity, route of repair and location of fistula were not significant prognostic factors for recurrence. Conclusions: Successful surgical repair of VVF require careful evaluation of various factors including number, size, previous attempts to surgical repair and etiology of VVF. One should opt for transabdominal route with delayed reconstruction and interposition of flap if above mentioned factors are present.